Evaluating the Photoprotective Effects of Ochre on Human Skin by In Vivo SPF Assessment: Implications for Human Evolution, Adaptation and Dispersal - Rifkin, Riaan F.; Dayet, Laure; Queffelec, Alain; Summers, Beverley; Lategan, Marlize; d’Errico, Francesco (PLOS ONE, 2015)
Archaeological indicators of cognitively modern behaviour become increasingly prevalent during the African Middle Stone Age (MSA). Although the exploitation of ochre is viewed as a key feature of the emergence of modern human behaviour, the uses to which ochre and ochre-based mixtures were put remain ambiguous. Here we present the results of an experimental study exploring the efficacy of ochre as a topical photoprotective compound. This is achieved through the in vivo calculation of the sun protection factor (SPF) values of ochre samples obtained from Ovahimba women (Kunene Region, Northern Namibia) and the Palaeozoic Bokkeveld Group deposits of the Cape Supergroup (Western Cape Province, South Africa). We employ visible spectroscopy, energy-dispersive X-ray fluorescence (ED-XRF), X-ray diffraction (XRD) and granulometric analyses to characterise ochre samples. The capacity of ochre to inhibit the susceptibility of humans to the harmful effects of exposure to ultraviolet radiation (UVR) is confirmed and the mechanisms implicated in the efficacy of ochre as a sunscreen identified. It is posited that the habitual application of ochre may have represented a crucial innovation for MSA humans by limiting the adverse effects of ultraviolet exposure. This may have facilitated the colonisation of geographic regions largely unfavourable to the constitutive skin colour of newly arriving populations.